2018
DOI: 10.1096/fj.201700780r
|View full text |Cite
|
Sign up to set email alerts
|

The histone demethylase KDM5A is required for the repression of astrocytogenesis and regulated by the translational machinery in neural progenitor cells

Abstract: Histone demethylases are known to play important roles in the determination of the fate of stem cells and in cancer progression. In this study, we show that the lysine 4 of histone H3 (H3K4), lysine-specific demethylase 5A (KDM5A) is essential for the repression of astrocyte differentiation in neural progenitor cells (NPCs), and its expression is regulated by translational machinery. Knockdown of KDM5A in NPCs increased astrocytogenesis, and conversely, KDM5A overexpression reduced the transcriptional activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(82 citation statements)
references
References 56 publications
3
76
0
Order By: Relevance
“…As previously described, 4EBP-dependent translational repression promotes NSC self-renewal and prevents differentiation [22]. However, it has been reported that MNK-mediated eIF4E phosphorylation is elevated in self-renewing neural progenitor cells (NPCs) and lost upon differentiation, in contrast to mTORC1 activity [33]. The effects of eIF4E phosphorylation on global translation in NPCs were not addressed but seem to strongly promote the expression of KDN5A, which is crucial for maintaining NPC stemness.…”
Section: The Mitogen-activated Protein Kinase (Mek) Pathwaymentioning
confidence: 91%
See 1 more Smart Citation
“…As previously described, 4EBP-dependent translational repression promotes NSC self-renewal and prevents differentiation [22]. However, it has been reported that MNK-mediated eIF4E phosphorylation is elevated in self-renewing neural progenitor cells (NPCs) and lost upon differentiation, in contrast to mTORC1 activity [33]. The effects of eIF4E phosphorylation on global translation in NPCs were not addressed but seem to strongly promote the expression of KDN5A, which is crucial for maintaining NPC stemness.…”
Section: The Mitogen-activated Protein Kinase (Mek) Pathwaymentioning
confidence: 91%
“…As described above, global translation in undifferentiated stem cells is generally maintained at a low level and needs to be tightly regulated. However, despite this dampening of global translational activity, stem cells need to sustain a proper expression level of key stemness factors in order to maintain their specific identities [7,[10][11][12]29,33]. Conversely, the expression of these factors must be repressed during differentiation while global protein synthesis increases.…”
Section: Mechanisms Regulating Translation In Stem Cellsmentioning
confidence: 99%
“…KD of KDM5A in NPCs increases astrocytogenesis and GFAP synthesis. Conversely, KDM5A over-expression reduces the transcriptional activity of the GFAP promoter (Kong, Kim, Lee, & Kim, 2018).…”
Section: Methylation Modificationmentioning
confidence: 98%
“…KD of KDM5A in NPCs increases astrocytogenesis and GFAP synthesis. Conversely, KDM5A over‐expression reduces the transcriptional activity of the GFAP promoter (Kong, Kim, Lee, & Kim, ). Moreover, KDM4A and KDM4C are essential for proper differentiation of neural stem cells into neurons and astrocytes.…”
Section: Expression Of Gfap and Its Regulationmentioning
confidence: 99%
“…Endogenous NSCs are used for cell therapy due to their capacity to differentiate and restore the loss of neurons [2][3][4][5]. The fate of NSC is regulated by extrinsic factors and the culture environments in addition to intrinsic mechanisms [6][7][8][9][10][11][12][13][14]. For example, intrinsic factors such as the basic helix-loop-helix proteins, Mash1, and Neurogenin2, are involved in the acquisition of neuronal cell fate [15][16][17].…”
Section: Introductionmentioning
confidence: 99%